Julius J. Bautista (2010). Figuring Catholicism: An ethnohistory of the Santo Niño de Cebu. Quezon City: Ateneo de Manila University. - Seng Guan, Yeoh (Social Science Diliman: A Philippine Journal of Society and Change; Vol 7 No 2 (2011))
none